ROLE OF LIVELIHOOD IN WOMEN EMPOWERMENT IN BIHAR - Kumar, Raushan; Singh, Shivendra (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The tradition of taking and giving help in any work has been going on since ancient times among the villagers of every state of India, 'the feeling of community' is the biggest feature of rural society. Since these rural farmers do not have any additional source of income other than farming, their income stops after 5 to 6 months of farming, due to which they have to mortgage their land and jewellery for emergency expenses because despite the wide network of bank branches, the villagers have very little access to them. But now many farmers have started getting solutions to their problems to some extent with the help of voluntary organizations. In the last few years, more emphasis has been laid on institutionalizing women's groups with economic goals as an important way to improve women's empowerment and economic outcomes in developing countries. Self-help groups (SHGs), savings groups, mother groups, health groups and community mobilization groups are examples of these programs. Economic empowerment of women is important for their personal success as well as the progress of their family, society and nation. This study shows how microfinance programs like Jeevika can be used to empower women. When a woman enrolls in a microcredit program, her sense of empowerment skyrockets.Jeevika Even if women who receive loans do not use the funds for income-generating activities, they still do so. Have more resources. Women who receive loans have greater access to resources, even if they do not use the funds for income-generating initiatives. In general, women actively encourage and facilitate social changes. Rather than being merely passive recipients of society's welfare-enhancing assistance. As a result, they may exhibit proactive behavior. Although women's development and empowerment are not the main objectives of the project, they are the key means of achieving it through the formation of women-based self-help groups in communities. This clearly shows how important women's roles are in the development process and achieving mutual empowerment.